Pierre George, Raymond Guglielmo, Bernard Kayser e Ives Lacoste, Geografía activa, Barcelona, Ariel, 1967, 414 p. - Richard, Rodolfo Alberto (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Geografía, 1969)

(untitled)
Fil: Richard, Rodolfo Alberto.